Pembenahan Muatan Kebijakan Pembangunan Hukum Nasional Melalui Policy Screening Tool Terhadap Rancangan Undang-Undang - Kholifah, Ayu (Jurnal Legislasi Indonesia, 2022)
Indonesia experienced a communication crisis in the legislative process that resulted in several laws being rejected by the public. The big demonstration against the ratification of the law began with the revision of the KPK Law, followed by the ratification of three other quite controversial laws, namely the amendment of Mineral and Coal Mining Law, the Constitutional Court Law, and the Job Creation Law. This condition is quite disturbing if it repeats itself in the future because it will be a ticking time bomb by continuously eroding public trust in the government. The law, which should be able to become social control, actually creates new problems and does not work effectively, because it does not accommodate the interests of the community, resulting in many rejections through demonstration actions. Representative democracy carried out by the legislature seems to need public assistance to make responsive laws that represent the public interests. This problem makes us aware that there must be improvements in the development of national laws by increasing public participation. This article is normative legal research that used qualitative analysis with a statute approach focused on procedures for the process of legislation. The results indicate that one of the efforts to optimize public participation in forming laws and regulations that do not get consensus from all the legislature’s members is by applying the Policy Screening Tool (PST). PST is a policy analysis tool that could be a parameter of whether a legal draft is feasible to be passed or not.Keywords: policy analysis, law development, screening tool, legal draft.